2017
DOI: 10.1007/s12160-017-9911-3
|View full text |Cite
|
Sign up to set email alerts
|

Observed Relationship Behaviors and Sleep in Military Veterans and Their Partners

Abstract: Background Emerging research has begun to examine associations between relationship functioning and sleep. However, these studies have largely relied on self-reported evaluations of relationships and/or of sleep, which may be vulnerable to bias. Purpose To examine associations between relationship functioning and sleep in military couples. This is the first research to examine associations between observed relationship behaviors and subjective and polysomnographically-measured sleep in a sample at-risk for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…We sought to expand existing research on the sleep-promoting effects of general perceived responsiveness by examining how daily responsiveness to capitalization (i.e., capitalization support) relates to subsequent sleep. We were interested in exploring this relationship maintenance process within a sample of military veterans and romantic partners, given the well-known challenges of military couples in regards to relationship functioning (Fillo et al, 2017). Additionally, we expand on existing research by examining intimacy and loneliness as explanatory mechanisms for responsiveness-sleep associations at the aggregate level.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to expand existing research on the sleep-promoting effects of general perceived responsiveness by examining how daily responsiveness to capitalization (i.e., capitalization support) relates to subsequent sleep. We were interested in exploring this relationship maintenance process within a sample of military veterans and romantic partners, given the well-known challenges of military couples in regards to relationship functioning (Fillo et al, 2017). Additionally, we expand on existing research by examining intimacy and loneliness as explanatory mechanisms for responsiveness-sleep associations at the aggregate level.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, 14% of the general population report that sleep disturbances due to the behaviour of their partner negatively affects their relationship [16]. Further, studies have reported impairments to daytime functioning and poorer relationship satisfaction when sleep is inadequate [17][18][19]. Therefore, inadequate sleep may also adversely impact the quality of the relationship between the on-call worker and their partner [20].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, greater relationship conflict is associated with poorer sleep quality (Hicks & Diamond, ), shorter sleep duration (for women), and difficulties falling asleep (El‐Sheikh, Kelly, & Rauer, ). Partners' hostile behaviors during conflict interactions also predict worse objective sleep quality (Fillo et al, ). Finally, changes in relationship status are also associated with sleep, such that women who remain involved in the same marital relationship for several years report comparatively better subjective sleep quality (Troxel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This growing literature supports the prediction that, over time , people involved in high‐quality, more stable relationships should experience better sleep outcomes than those involved in low‐quality, less stable relationships. Yet prior research on relationships and sleep has focused on either one‐time assessments within a current relationship (e.g., conflict behaviors in a relationship; Fillo et al, ) or over‐time assessments of a single relationship construct (e.g., changes in relationship status; Troxel et al, ). One possibility, therefore, is that associations between relationships and sleep may partly reflect ongoing patterns of relationship experiences and individual competencies rather than solely reflecting the nature and qualities of one's current relationship.…”
Section: Introductionmentioning
confidence: 99%